Long‐term data on entecavir treatment for treatment‐naive or lamivudine‐resistant chronic hepatitis B infection in kidney transplant recipients. Issue 5 (18th July 2019) - Yap, Desmond Y. H.; Tang, Colin; Fung, James Y. Y.; Seto, Wai‐Kay; Ma, Maggie K. M.; Choy, Bo Ying; Chan, Tak Mao
Abstract: Introduction: Entecavir (ETV) showed short‐term efficacy and safety in HBsAg‐positive kidney transplant recipients (KTRs), but long‐term data are lacking. Methodology: We retrospectively reviewed 30 HBsAg‐positive KTRs who received ETV during 2007‐2017. Results: Eighteen treatment‐naïve (Group I) and 12 lamivudine‐resistant (Group II) patients received ETV for 48.4 ± 35.2 and 66.0 ± 26.0 months, respectively. Both groups show significant HBV DNA decline, but Group I achieved earlier undetectability after 11.9 ± 9.6 months (compared with 28.8 ± 24.2 months in Group II, P  = .033). Group I showed higher rates of undetectable HBV DNA (89%, 94%, 94%, 100%, and 100% at 12, 24, 36, 48, and 60 months, respectively, compared with 25%, 50%, 50%, 91%, and 91% in Group II, P  = .003). ALT normalized after 6.0 ± 1.9 and 6.8 ± 2.1 months in Group I and Group II, respectively. Four patients (33.3%) in Group II developed drug resistance (2 had persistent viraemia and 2 had virological breakthrough, at 40.3 ± 15.0 months). Group II showed higher liver stiffness after 5 years (7.7 ± 4.1 kPa, compared with 5.0 ± 1.6 kPa in Group I, P  = .046) and incidence of cirrhosis (4 patients [33.3%], compared with 1 [5.6%] patient in Group I, P  = .049). Two patients (one in each group) developed hepatocellular carcinoma. Renal allograft function remained stable during follow‐up of 63.2 ± 33.4 months for both groups. There was no difference in patient and graft survival between two groups at 5 years ( P  = .62 and .36, respectively). Conclusion: ETV showed favorable long‐term efficacy and tolerability in treatment‐naïve KTRs. One‐third of lamivudine‐resistant subjects showed non‐response or viral breakthrough after ETV treatment.